1999
DOI: 10.1136/jmg.36.10.771
|View full text |Cite
|
Sign up to set email alerts
|

Specific polymorphisms in the RETproto-oncogene are over-represented in patients with Hirschsprung disease and may represent loci modifying phenotypic expression

Abstract: Hirschsprung disease (HSCR) is a common genetic disorder presenting with functional intestinal obstruction secondary to enteric aganglionosis. HSCR can be familial or sporadic. Although five putative susceptibility genes have been identified, only germline mutations in the RET proto-oncogene account for a significant minority (up to 50%) of familial HSCR; 3% of sporadic HSCR in a population based series carry RET mutations. From 1998 to February 1999, we prospectively ascertained 64 cases of sporadic HSCR from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
103
1
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 20 publications
15
103
1
10
Order By: Relevance
“…Moreover, it has been reported that a neutral germline sequence variance S836S RET may somehow predispose to sporadic MTC, especially those that harbour somatic M918T mutation . A highly significant association of RET polymorphisms, specifically the variant A45A, with Hirschsprung disease has also been observed (Borrego et al, 1999, Genetics and Genomics 2000; Fitze et al, 1999). Taking into account these and our present data, we suggest that the higher frequency of CCH observed in the irradiated thyroid glands of the patients bearing in their tumours a G691S RET SNP, may be an effect of the RET allele (or haplotype) on which the sequence variant has occurred.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, it has been reported that a neutral germline sequence variance S836S RET may somehow predispose to sporadic MTC, especially those that harbour somatic M918T mutation . A highly significant association of RET polymorphisms, specifically the variant A45A, with Hirschsprung disease has also been observed (Borrego et al, 1999, Genetics and Genomics 2000; Fitze et al, 1999). Taking into account these and our present data, we suggest that the higher frequency of CCH observed in the irradiated thyroid glands of the patients bearing in their tumours a G691S RET SNP, may be an effect of the RET allele (or haplotype) on which the sequence variant has occurred.…”
Section: Discussionsupporting
confidence: 75%
“…It may be suggested that the GGT?AGT polymorphism causes the creation of a cryptic splice donor, splice acceptor or splice enhancer, therefore leading to an altered protein that may contribute to the development of C-cell hyperplasia. Similar mechanisms have been previously hypothesised in the cases of polymorphisms associated with sporadic MTC and Hirschsprung disease (Borrego et al, 1999;Fitze et al, 1999;Gimm et al, 1999). Unfortunately, RNA from our radio-induced thyroid tumours was not available to test this hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding S904S polymorphism, also detected in the presented patient, strong co-segregation with G691S polymorphism has already been demonstrated (Gil et al 2002, Robledo et al 2003. Both polymorphisms have been shown to be under-represented in Hirschsprung's disease (HSCR, OMIM 142623) patients compared with controls, thus suggesting that they might protect against the development of HSCR (Borrego et al 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Uma possível influência de polimorfismos do RET na doença de Hirschsprung (DH) foi também investigada (68). A DH é uma desordem genética que cursa com obstrução intestinal funcional secundária a aganglionose entérica e que pode estar associada a uma mutação inativadora do RET.…”
Section: Polimorfismos No Carcinoma Medular De Tireóideunclassified
“…Os autores observaram uma maior freqüência dos polimorfismos A45A e L769L comparada à população controle. De outro modo, os polimorfismos G691S e S904S apresentaram uma freqüência menor entre os pacientes com DH comparado aos controles (68).…”
Section: Polimorfismos No Carcinoma Medular De Tireóideunclassified